Consuming nature: Antarctica, penguins and pollution. - Tomaselli, Keyan G. (Critical Arts: A South-North Journal of Cultural & Media Studies, 2012)
Non-smokers’ responses towards smokers on an Antarctic cruise provide the narrative thread against which broader environmental issues and passenger behaviour are debated. The study, conducted over a two-week period in 2009, applies auto-ethnography in examining contradictory tourist and crew behaviour with regard to the ship's internal and external environments. The ways in which designated smoking areas functioned to exclude the majority of passengers from common spaces, is examined. Simultaneously, the narrative takes the reader on a journey of how the study of responses to smoking gained in momentum as it began to address much broader issues of environmental degradation, environmental law and sustainable tourism.